المقاربات النظــرية للتربــية البيئــية - طويل, فتيحة (Sciences de l'Homme et de la Société, 2016)
تحاول هذه الدراسة إبراز مختلف الاتجاهات النظرية السوسيولوجية التي تتناول العلاقة بين الإنسان والبيئة، والتأثيرات المتبادلة وموقفها من البيئة ونظامها، وإستراتجية اقترابها من التربية البيئية وتنمية الشعور بالمسؤولية اتجاه قضايا البيئة، والالتزام بالمحافظة عليها وحل مشكلات البيئة، لتحقيق التنمية المستدامة. This study tries to know the different theoretical, sociological directions that takes into consideration the relation between human and environment with the exchangeable  influences and the is opinions toward environment and its system with the strategy that makes them closely to the environmental education and helps them to grow up the responsible feeling toward environmental cases, take care of environment and solve the different problems to satisfy the continuous progressing.